A comparison between nucleus pulposus-derived stem cell transplantation and nucleus pulposus cell transplantation for the treatment of intervertebral disc degeneration in a rabbit model. (April 2016) - Chen, Xiaofeng; Zhu, Lixin; Wu, Guofeng; Liang, Zhihao; Yang, Leiluo; Du, Zhicai
Abstract: Introduction: In recent years, nucleus pulposus cell (NPC) transplantation has been used to treat intervertebral disc degeneration (IDD); however, the degenerative nature of NPCs influences its effectiveness. Nucleus pulposus-derived stem cells (NPSCs), which are self-renewing, have high expansion potential and can adapt to the intervertebral disc (IVD) microenvironment and may have a better regenerative capacity, which is favourable for treating IDD. The aim of this study was to compare the effectiveness of transplantation with NPSCs and NPCs on the regeneration of the IVD in rabbit models. Methods: NPSCs and NPCs were isolated from human degenerate nucleus pulposus tissue by differential adhesion method, and stem cell surface markers were detected by flow cytometry. Degenerative discs in rabbits were randomly distributed into three groups: NPSCs, NPCs and vehicle control group; the normal discs served as the normal control group. Cells of the P3 generation were prepared for transplantation. About 20 μl of cell suspension (NPSCs or NPCs) or DMEM was injected into corresponding discs, while the normal discs were left untreated. After 8 weeks, disc height was evaluated using X-ray, water content was evaluated by MRI, and gene and protein expression levels of collagen II and aggrecan in the nucleus were determined by real-time PCR and ELISA. Results: NPCs and NPSCs from the P3 generation were polygonal and spindle-shaped, respectively. Both NPSCs and NPCs strongly expressed surface markers CD73, CD90, and CD105 and weakly expressed CD34 and CD45. The relative rates of expression of CD73, CD90, and CD105 were higher in NPSCs than in NPCs. After 8 weeks, X-ray results showed no significant difference in disc height index among the groups (p > 0.05). MRI revealed that the intensity of the nucleus pulposus signal was increased in NPSCs (p < 0.05). The results from PCR and ELISA demonstrated that NPSCs promoted gene and protein expression of aggrecan instead of collagen II (p < 0.05). Conclusion: Compared to NPCs, NPSCs harvested by differential adhesion method displayed a higher positive rate of stem cell surface markers and showed superior regenerative effectiveness for treating IDD in rabbit models. Therefore, NPSCs are potential candidates for cell therapy for the regeneration of the IVD. Highlights: Both nucleus pulposus-derived stem cells (NPSCs) and nucleus pulposus cells (NPCs) expressed stem cells surface markers. NPSCs harvested by differential adhesion method had higher mesenchymal stem cells surface markers than NPCs. NPSCs transplantation showed better regenerative effects for intervertebral disc degeneration compared with NPCs.